Regulation of E-Cigarettes in the United States and Its Role in a Youth Epidemic - Mark A. Gottlieb (MDPI AG, 2019)
During the first decade of federal regulation of electronic nicotine delivery systems (ENDS), the e-cigarette industry has rapidly grown. Recently, the U.S. Surgeon General and Commissioner of the Food and Drug Administration each declared the rapid rise in rates of youth using these products to be an “epidemic.” While a foundational basis for regulating ENDS has been in effect since 2016, deferred enforcement has contributed to acute rise in use by youth. The Agency has undertaken several initiatives to address the problem and warned manufacturers that if current youth trends continue, it will be “game over.”